War stories ii eaudiobook Heroism in the pacific. - North, Oliver (Recorded Books Inc., 2019)
New York Times best-selling author Oliver North, host of FOX News Channel's top-rated War Stories program, describes the remarkable accomplishments of the heroic men who fought in the Pacific theater of World War II. The American and Japanese veterans of such terrible campaigns as Guadalcanal and Iwo Jima shared their stories with North, who presents them here in the soldiers' own words. More than a fascinating history of combat, War Stories II stands as a testament to the unmatched valor and bravery of an extraordinary generation.